The Relevance of Online Social Relationships Among the Elderly: How Using the Web Could Enhance Quality of Life? - Benvenuti, Martina; Giovagnoli, Sara; Mazzoni, Elvis; Cipresso, Pietro; Pedroli, Elisa; Riva, Giuseppe (Frontiers in Psychology, 2020)
This observational study analyzes the impact of Internet use on the quality of life and well-being of the elderly. Specifically, it seeks to understand and clarify the effects of Internet use on relationships in terms of self-esteem, life satisfaction and online and offline social support in a sample of senior and elderly Italian people (over 60 years of age). A cohort of 271 elderly people (133 males, 138 females) aged between 60 and 94 years old participated in the study: 236 were Internet Users while the other 35 were Non-Internet Users. The results showed that the time elderly people spend online has a negative effect on their perception of Offline Social Support (Offline Emotional and Informational, and Offline Affective Social Support) and a positive effect on their perception of Online Social Support (particularly on Online Positive Social Interactions). Surprisingly, Internet Use among elderly people seems to impact positively on the perception of Offline Social Support. Indeed, Elderly Internet Users have a more positive perception of Offline Social Support (particularly Offline Positive Social Interactions and Offline Affective Social Support) than Non-Internet Users. A discussion of this finding is provided, positing that the Internet seems to represent the technological side of a functional organ that allows the elderly to stay in closer touch with their family and friends, and in doing so to also overcome some age-related difficulties.